The Solubility of Cr-Organic Produced by Hydrolysis, Bioprocess and Bioremediation and its Effect on Fermented Rate, Digestibility and Rumen Microbe Population (in vitro) - Tanuwiria, UH; Santosa, U; Yulianti, A; Suryadi, U (ANIMAL PRODUCTION, 2010)
The research was conducted to study the production of organic chromium from the leather tanning waste and its effect on in vitro rumen fermentation activities.  The research was divided into two phases. The first phase was production of organic chromium by alkali hydrolysis, S cereviceae bioprocess, and duckweed bioremediation that perceived solubility in neutral and acid solution. The second phase was the supplementation of organic-Cr in ration seen from in-vitro fermented rate, digestibility and microbe rumen population. Research was conducted experimentally using 4x4 factorial patterns, on the basis of Completely Randomized Design (CRD) with three replications in each experimental unit. The first factor was the type of organic-Cr and the second factor was the supplement in ration at four levels, 1, 2, 3 and 4 ppm. The results of this research indicated that organic chromium can be synthesized by alkali hydrolysis, S cereviseae bioprocess and the activity of duckweed bioremediation.  Among the three of processes referred, the highest level of Cr was obtained from S cereviseae bioprocess that was originated from leather-tanning waste.  The levels of organic-Cr that was resulted from alkali hydrolysis, bioprocess from Cl3Cr.6H2O, bioprocess from Cr leather-tanning waste, and from duckweed bioremediation were 354, 1011, 3833 and 310 mg/kg, respectively. Organic-Cr characteristic of each product has relatively similar in ferment ability, dry matter and organic matter digestibility and rumen ecosystem. There is an indication that dry matter and organic matter digestibility and rumen microbe population in ration that was added with organic Cr from alkali hydrolysis was higher than other supplements. (Animal Production 12(3): 175-183 (2010)Key  Words: organic-Cr, rumen fermentation activities, rumen microbe population